Gastro-duodenal injury associated with intake of 100-325 mg aspirin daily. Issue 815 (September 1993) - Oren, R.; Ligumsky, M.; Lysy, J.; Gonzales, J.; Zimmerman, J.
Abstract : During the year 1991, 43 patients with upper gastrointestinal bleeding and one with severe epigastric pain associated with intake of non-steroidal anti-inflammatory drugs were admitted for emergency endoscopy to our unit. Fourteen patients (33%) had been treated with 100-325 mg aspirin daily, 11 of them for at least one year. The mean age of this group was 71. Only two patients had a previous history of peptic ulcer. Five patients used anticoagulants or antiplatelet drugs concomitantly with aspirin. The endoscopic diagnosis of the sources of bleeding was erosive gastritis in eight patients, gastric ulcer in four, duodenal ulcer in five and oesophageal ulcer in one. Our results support findings by other groups, showing that doses of aspirin as low as 75 mg daily should be used in the management of elderly patients with thrombo-embolic disease.